ChemInform Abstract: The Synthesis of Cyclohexenone Using L‐Proline Immobilized on a Silica Gel Catalyst by a Continuous‐Flow Approach. Issue 48 (2nd December 2014) - Zhi, Cong; Wang, Jiaqing; Luo, Bin; Li, Xinming; Cao, Xueqin; Pan, Yue; Gu, Hongwei
Abstract 17 Cyclohexene derivatives of type (III) are prepared by a continuous‐flow approach using L‐proline immobilized on silica gel as catalyst.